2023
DOI: 10.3390/tomography9050134
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality and Radiation Dose of Conventional and Wide-Field High-Resolution Cone-Beam Computed Tomography for Cerebral Angiography: A Phantom Study

Satoru Kawauchi,
Koichi Chida,
Yusuke Hamada
et al.

Abstract: There has been an increase in the use of interventional neuroradiology procedures because of their non-invasiveness compared to surgeries and the improved image quality of fluoroscopy, digital subtraction angiography, and rotational angiography. Although cone-beam computed tomography (CBCT) images are inferior to multi-detector CT images in terms of low-contrast detectability and lower radiation doses, CBCT scans are frequently performed because of their accessibility. This study aimed to evaluate the image qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…In the head CBCT scans, the DAP value in the FOV48 cm group was 1.28 times higher than that in the FOV42 cm group. Similar findings have been reported by Kawauchi et al [ 16 ], who found that the DAP value in their FOV27 cm group was 1.44 times higher than that in their FOV22 cm group. However, it is worth noting that their study showed equal RAK values between the two FOV size groups, differing from our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the head CBCT scans, the DAP value in the FOV48 cm group was 1.28 times higher than that in the FOV42 cm group. Similar findings have been reported by Kawauchi et al [ 16 ], who found that the DAP value in their FOV27 cm group was 1.44 times higher than that in their FOV22 cm group. However, it is worth noting that their study showed equal RAK values between the two FOV size groups, differing from our results.…”
Section: Discussionsupporting
confidence: 91%
“…While previous studies have explored the role of CBCT in interventional procedures [ 3 , 6 , 10 ], there has been limited research specifically focusing on the radiation dose associated with CBCT image acquisition. Some studies have employed phantoms to estimate the dose of CBCT, but the corresponding results have shown significant variations due to the different methodologies used for estimating the effective dose (ED) [ 12 , 13 , 14 , 15 , 16 , 17 ]. Direct measurement of ED may be affected by differences in phantom size or material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation